2015
DOI: 10.1177/0276237415597390
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Music and Visual Art Preferences and Some Personality Traits

Abstract: The aim of this research was to investigate the relationship between musical and visual art preferences, and the role of personality traits in predicting preferences for different musical styles and visual art motives. Participants were asked to fill out the following instruments: Questionnaire of music preferences, Questionnaire of visual art preferences, Questionnaire for personality traits International Personality Item Pool [IPIP]; the Arnett Inventory of Sensation Seeking. Results showed that most partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
5
20
1
Order By: Relevance
“…Similarly, studies on personality and music preferences revealed that Conscientiousness is inconsistent in predicting music preferences. Previous studies reported no significant correlation between Conscientiousness and any music preference dimensions (Brown, 2012;Dys et al, 2017;Ercegovac et al, 2015;Langmeyer et al, 2012;Livosky et al, 2012;Upadhyay, Shukla, & Chakraborty, 2017). To explain this, McManus and Furnham (2006) demonstrated that Conscientious individuals have a narrow artistic view and less interest in visual and general art activities, inclusive of music.…”
Section: Relationship Between Personality and Music Preferencesmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, studies on personality and music preferences revealed that Conscientiousness is inconsistent in predicting music preferences. Previous studies reported no significant correlation between Conscientiousness and any music preference dimensions (Brown, 2012;Dys et al, 2017;Ercegovac et al, 2015;Langmeyer et al, 2012;Livosky et al, 2012;Upadhyay, Shukla, & Chakraborty, 2017). To explain this, McManus and Furnham (2006) demonstrated that Conscientious individuals have a narrow artistic view and less interest in visual and general art activities, inclusive of music.…”
Section: Relationship Between Personality and Music Preferencesmentioning
confidence: 92%
“…It also shows a tendency towards positive behaviour that diverges from hostility. Individuals who possess a strong trait of Agreeableness are perceived as warm and friendly and harbouring good intentions (Ercegovac et al, 2015). Conversely, less agreeable individuals are perceived negatively as harsh and hostile (Livosky, Stevens, Hoff, & Surawski, 2012).…”
Section: Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although a considerable amount of studies focuses on the characteristics of personality that are related to musical tastes (Cleridou & Furnham, 2014;Ercegovac, Dobrota, & Ku s cevi c, 2015;Rentfrow & Gosling, 2003;Sch€ afer & Mehlhorn, 2017), much of the research has omitted to examine thoroughly the association between personality traits and the multiple ways in which music is used. Moreover, although personal values are a factor for deserving additional attention, previous research has neglected to inquire into the effects of individuals' values on different functions of music.…”
mentioning
confidence: 99%